AI-Generated Art: Insights from Professional Tradigital Artists - Cervantes, Sunshin; Bautista, Maderic; Fabon, Kane (12th International Scholars Conference 2025, 2026)
Artificial intelligence (AI) is increasingly influencing how visual artists create. This study examined how professional tradigital artists—those who blend traditional and digital media—engage with AI-generated art in their current practices. Using a qualitative case study approach, five professional artists were interviewed, and the data were analyzed thematically through the lens of Piaget’s Constructivist Learning Theory. Four key themes emerged: (1) AI as a Tool for Efficiency, (2) AI’s Contentious Role in the Art Community, (3) Balancing Traditional and Digital Practices, and (4) Human Creativity is Irreplaceable. Participants revealed that AI is integrated mainly for workflow optimization, not as a substitute for human creativity. Artists emphasized that while AI can enhance productivity and provide visual assistance, emotional depth, originality, and intentionality remain uniquely human attributes essential to art. The study offers timely insight for contemporary artists, educators, and institutions navigating AI in the arts. It is recommended that current artists use AI critically as a supplementary tool and that educational institutions integrate AI discussions into art programs. Furthermore, this study encourages future researchers to explore a quantitative approach to gather broader, statistically grounded perspectives on the role of AI in art.